Asyndetic compound sentence in the Ukrainian folk riddle imagery (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article studies the Ukrainian riddle as a unique type of folk art that by means of verbalized national and cultural stereotypes reflects the ethnic singularity of the Ukrainians, their world perception and its rendering in the form words, word combinations and set phrases. The Ukrainian folk riddle is an element of the cultural code of the Ukrainian speaking personality and a source of oxpression of language peculiarities of the Ukrainian literary speech. The Ukrainian folk riddle is a linguocultural mini text that is considered to be an important language unit for studying the relations between the language and the culture, the language and the poetic way of thinking of people. The texts of the Ukrainian riddles have always been the subject of researches in such field as folklore studies, linguistics, linguostylistics, stylistics, cultural studies and rhetoric. The peculiarity of the riddle as a singular folklore genre is concentrated on a certain subject, in particular, on the selection of the riddle object, denotation to which the mini text is dedicated. Moreover, its peculiar feature is based on laconism, compression of the expressed thought, content paradoxicality and clear syntactical form of the text. Studying a riddle as a literary element of oral tradition, as an individual genre that was created within the history, the researchers have determined two main elements in the structure of the riddle: figurative, descriptive (expressed by the speaker) and the answer (of the listener) that is the solution of the riddle. Nevertheless, the first element is considered more attractive for making linguistic researches. It is known that asyndetic sentences are quite popular in the modern speech. On the one hand, the classifications of these sentences are based on the sense relations between the elements (the asyndetic sentences correspond to the conjunctive ones), on the other hand, they are based on the intonation peculiarities of the sentences of each type. The main attention is paid to the fact that the constructions with asyndetic relations in the figurative element of the riddle are mostly observed in the compound sentences. They are represented by all the structural types and among them the combinations that have comparative meaning are mostly widespread. As a general matter, the comparison of the parallel syntactical constructions that have contrary content create the riddles with contradictory meaning which are considered riddles of paradoxical type. In the asyndetic sentences which have enumerating and comparative meanings we can seldom observe free word order because of the rules and norms of rhythmical system of the language and lexical composition of the figurative part of the riddle. It has been concluded that there is rather a small number of riddles created due to the asyndetic sentence patterns with semantic relations expressing conditions and explanations.
Keywords: folklore; oral tradition; the Ukrainian folk riddle; asyndetic compound sentence; figurative element of the riddle